The Effect of Parenting Styles, Self-Control, and Social Media Use on Student Politeness - Alawiyah, Ferawati Fajrin; Prasetiyo, Wibowo Heru (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study investigates how parenting styles, self‑control, and social media use influence the politeness of undergraduate students at Muhammadiyah University of Surakarta. By identifying these relationships, the research aims to shed light on factors contributing to the observed decline in polite behavior among adolescents and inform interventions to promote respectful communication. Methodology: Adopting a quantitative correlational design, the study surveyed 370 S1 students across multiple faculties at Universitas Muhammadiyah Surakarta (UMS). Standardized questionnaires measured perceived parenting style (authoritative, authoritarian, permissive), individual self‑control levels, patterns of social media usage, and self‑reported politeness behaviors. Data were analyzed using multiple regression techniques to assess the strength and significance of each predictor’s effect on student politeness. Results: The analysis demonstrated that all three independent variables—parenting styles, self‑control, and social media use—exerted positive, statistically significant effects on students’ politeness (p < 0.05). Authoritative parenting and higher self‑control were particularly strong predictors, while balanced, purposeful social media engagement also correlated with more courteous online and offline interactions. Applications/Originality/Value: By empirically linking family dynamics, individual regulation skills, and digital habits to polite conduct, this study offers a comprehensive framework for educators, counselors, and policymakers aiming to foster respectful behavior. Its findings can guide parent‑education programs, campus‑based self‑control workshops, and digital‑literacy initiatives, while providing a theoretical foundation for future research on adolescent social etiquette in digital contexts.